Precision agronomic packages to enhance durum wheat productivity. Project report - Nigir, Bogale; Terefe, Hailu; Tilahun, Mulugeta; Kidane, Yosef Gebrehawaryat; Fadda, Carlo; Mengistu, Dejene Kassahun (2025)
Input management is among the critical yield-limiting factors in crop production. Recognizing that blanket agronomic recommendations for bread wheat are unsuitable for durum wheat production. Thus, we identified optimal sowing dates and seed rates specifically for farmer-preferred varieties in Gimbichu (East Shewa). According to the current trials, sowing data of July 27 with a seed rate of 150 kg ha-1 provided the highest grain yield of 3.9 t ha-1, 77% above the national durum wheat average. Varietal differences were also evident, with Melfa (white seed) producing more biomass (valuable for livestock feed), while Geregera (black seed) gave slightly higher grain yield and greater stability under late-sowing stress, indicating the advantage of diversified varietal options for farmers to grow for preferred traits. Likewise, fertilizer trials further emphasized the need for crop- and site-specific nutrient management. For variety Melfa, the combination of 100 kg ha-1 NPS + 125 – 150 kg ha-1 urea (split-applied) maximized grain yield of 3.02 t ha-1 (165% increase over unfertilized controls) while avoiding lodging risks. Crucially, NPS was found essential to unlock urea responsiveness, confirming that balanced N–P–S nutrition is non-negotiable on Ethiopian Vertisols. To identify complementing options, an inorganic input and organic–inorganic integration trial showed that ½ farmyard manure + ½ inorganic fertilizer boosted Melfa’s yield by 34% over sole organic treatments, revealing synergistic effects on moisture retention, phosphorus availability, and soil health. Meanwhile, the improved variety Mangudo achieved 3.24 t ha-1 with full inorganic inputs, underscoring the importance of matching genotype to management. In summary, this research establishes that sustainable intensification of durum wheat in Ethiopia stand on three pillars: (1) varietal diversification that offers farmers functional choices aligned with their livelihood strategies; (2) precision agronomy: sowing date, seed rate, and fertilizer regime, calibrated to specific varieties and local soil–climate conditions; and (3) integrated nutrient management that leverages synergies between organic and inorganic sources to boost productivity while enhancing soil health. Together, these approaches not only lift well above national averages but also build resilience against climate variability, reduce input costs, minimize environmental externalities, and strengthen farm-level food and feed security. By centering farmer knowledge and ecological principles, the findings offer a scalable, resilient, and ecologically sound pathway for durum wheat systems in Ethiopia, an essential contribution to national food security and climate adaptation in an era of accelerating uncertainty.